STUDI PERANCANGAN PISAU PADA MESIN PENCACAH PLASTIK MENGGUNAKAN FINITE ELEMENT ANALYSIS - Rizqi Ilmal Yaqin; Mega Lazuardi Umar; Sigiet Haryo Pranoto; Angger Bagus Prasetiyo; Bambang Hari Priyambodo (P3M Politeknik Negeri Indramayu, 2021)
The amount of plastic waste each year will increase by 10% every year which is a problem for a country. Therefore, proper processing of plastic waste needs to be done. Before being processed into plastic waste processing, it is necessary to have a chopping process using a plastic chopping machine. The plastic chopping machine has an important component, namely the chopping knife. Before carrying out the knife manufacturing process, it is necessary to validate the design of the blade that is used with its loading. Model simulation using software is one way to quickly validate the model. This study aims to determine the effect of loading variations on stress, strain, deformation and safety factors of the model. The use of ANSYS R17.2 software is used to analyze the chopping machine knife model with a variation of 5kg / hour, 10kg / hour, 20kg / hour and 50kg / hour capacities. The result is that the stress, strain and deformation parameters have an increase in value with increasing loading variations. The greatest values of stress, strain and deformation are in the variation of 50kg / hour respectively 64.995 Pa; 336.76 and 56,358 x 10-11mm. The value of the safety factor for all variations of loading has a value of 15. The value of the safety factor means that the design of the plastic chopping knife is safe to use up to a loading of 50kg / hour